Essays in honor of Aman Ullah - Gonza<U+0301>lez-Rivera, Gloria; Hill, R. Carter; Lee, Tae-Hwy.; Emerald eBooks (Bingley, U.K. : Emerald, 2016)
Volume 36 of Advances in econometrics recognizes Aman Ullah's significant contributions in many areas of econometrics and celebrates his long productive career. The volume features original papers on the theory and practice of econometrics that is related to the work of Aman Ullah. Topics include nonparametric/semiparametric econometrics; finite sample econometrics; shrinkage methods; information/entropy econometrics; model specification testing; robust inference; panel/spatial models.Advances in Econometrics is a research annual whose editorial policy is to publish original research articles that contain enough details so that economists and econometricians who are not experts in the topics will find them accessible and useful in their research.
A selective review of Aman Ullah's contributions to econometrics / Yong Bao ... [et al.] -- Semiparametric estimation of partially linear varying coefficient panel data models / An Yonghong, Hsiao Cheng, Li Dong -- Testing for spatial lag and spatial error dependence in a fixed effects panel data model using double length artificial regressions / H. Badi Baltagi, Long Liu -- Long-run effects in large heterogeneous panel data models with cross-sectionally correlated errors / Alexander Chudik ... [et al.] -- Semiparametric estimation of partially linear dynamic panel data models with fixed effects / Liangjun Su, Yonghui Zhang -- Finite-sample bias of the conditional gaussian maximum likelihood estimator in ARMA models / Yong Bao -- Finite sample bias corrected IV estimation for weak and many instruments / Matthew Harding, Jerry Hausman, Christopher J. Palmer -- On the construction of prior information : an info-metrics approach / Amos Golan, Robin L. Lumsdaine -- The wage premium of naturalized citizenship / Esfandiar Maasoumi, Yifeng Zhu -- Causality and Markovianity : information theoretic measures / Eric Renault, Daniela Scida<U+0301> -- A likelihood-free reverse sampler of the posterior distribution / Jean-Jacques Forneron, Serena Ng -- A vector autoregressive moving average model for interval-valued time series data / Ai Han ... [et al.] -- Inference in near-singular regression / Peter C.B. Phillips -- Multivariate local polynomial estimators : uniform boundary properties and asymptotic linear representation / Yanqin Fan, Emmanuel Guerre -- Model averaging over nonparametric estimators / Daniel J. Hendersen, Christopher F. Parmeter -- Smoothness : bias and efficiency of nonparametric kernel estimators / Yulia Kotlyrova, Marcia M.A. Schafgans, Victoria Zinde-Walsh -- A class of nonparametric density derivative estimators based on global Lipshitz conditions / Kairat Mynbaev, Carlos Martins-Filho, Azziza Aipenova -- Local polynomial derivative estimation : analytic or Taylor? / Jeffrey S. Racine -- A simple consistent nonparametric estimator of the Lorenz curve / Yu Zhang, Ximing Wu, Qi Li.
Keywords: Ullah, Aman; Business & Economics -- Economics -- Macroeconomics; Econometrics; Econometrics; Electronic books